2009
DOI: 10.3102/0002831209349460
|View full text |Cite
|
Sign up to set email alerts
|

Student Characteristics, Pre-College, College, and Environmental Factors as Predictors of Majoring in and Earning a STEM Degree: An Analysis of Students Attending a Hispanic Serving Institution

Abstract: At a Canadian university, 177 students completed a baseline questionnaire and six monthly Web-based questionnaires about their sexual behavior and positive and negative affect. The results revealed that psychosocial maturity, attitudes toward sex, prior sexual experience, and living arrangements influenced the relationship between sex and affect. When sexual behavior was reported, the more psychosocially mature students reported more positive affect than did the less mature students. The students with more per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
328
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 380 publications
(352 citation statements)
references
References 34 publications
21
328
1
2
Order By: Relevance
“…Similarly, Hurtado et al (2006) found Mexican American, Puerto Rican and American Indian students take fewer mathematics, physics, and biological sciences courses, or gatekeeper courses, as compared to their White and Asian counterparts. Crisp, Nora, and Taggart (2009) found minority students more likely to drop out of such gatekeeper courses as compared to their White counterparts. Minority women have the lowest persistent rate in STEM studies, according to Smyth and McArdle (2004), which they attribute to the intersection between gender and ethnicity, or what many refer to as the "double bind".…”
Section: The Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Hurtado et al (2006) found Mexican American, Puerto Rican and American Indian students take fewer mathematics, physics, and biological sciences courses, or gatekeeper courses, as compared to their White and Asian counterparts. Crisp, Nora, and Taggart (2009) found minority students more likely to drop out of such gatekeeper courses as compared to their White counterparts. Minority women have the lowest persistent rate in STEM studies, according to Smyth and McArdle (2004), which they attribute to the intersection between gender and ethnicity, or what many refer to as the "double bind".…”
Section: The Problemmentioning
confidence: 99%
“…In 2012.2% of engineering degrees were awarded to females with a mere 3.1% of these awarded to women from underrepresented minorities (National Science Foundation [NSF], 2015). The low representation of women, and Latinas specifically, has been the topic of inquiry by various organizations and institutions that have aggressively reached out to females (National Research Council, 1991;Crisp, Nora, and Taggart (2009) argue university campus cultures can be unwelcoming and competitive, which can further alienate minorities from full participation and may contribute to others resisting entrance to these possibly hostile and alienating environments.…”
Section: The Problemmentioning
confidence: 99%
“…Pre-college, engineering programs have been shown to attract students to engineering and other STEM careers (Crisp, Amaury & Taggart, 2009;Delci, 2002;Yelamarthi & Mawasha, 2008). Our goal is for our teachers to offer varied, hands-on projects in their engineering classrooms that are practical, but also community minded, artful, or even musical.…”
Section: Engr 102 Hs: Introduction To Engineeringmentioning
confidence: 99%
“…In an attempt to improve schools through stricter accountability measures, high stakes testing has been implemented throughout grades K-12 in several subject areas including science (though it is only required to be tested once in grades [9][10][11][12]. Although the law succeeded in highlighting disparities in educational achievement for traditionally underserved students, there have been negative consequences, with some studies reporting that science has suffered from a disproportionate emphasis on reading and mathematics [4,5].…”
Section: Introductionmentioning
confidence: 99%